Titanium material, titanium container, and method for manufacturing titanium material
Patent Information
- Application Number
- JP2023125440
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-01
AI Technical Summary
【0014】 本発明は上述のように構成したから、これまでにないチタン材、チタン製の容器およびチタン材の製造方法となる。
Smart Images

Figure 2025021616000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a titanium material, a titanium container, and a method for manufacturing the titanium material. [Background technology]
[0002] The applicant has filed a patent application relating to a titanium vacuum insulated double container as disclosed in, for example, Patent Document 1. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5297436 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention was completed as a result of further research and development by the inventors, who discovered conditions for a titanium material surface that has reduced gloss, is resistant to fingerprint smudges, and has a refined texture with a gray base color. It is an object of the present invention to provide an unprecedented titanium material, a titanium container, and a method for manufacturing titanium material. [Means for solving the problem]
[0005] The gist of the present invention will now be described with reference to the accompanying drawings.
[0006] A titanium material having a titanium carbide layer on a surface thereof, The titanium carbide layer has a thickness of 5 μm or more. 10μm or less The arithmetic mean roughness (Ra) of the surface is 0.90μm or more. 1.70μm or less and The average equivalent circular diameter of the area in which the twin crystals are aligned in the crystal grains containing the twin crystals confirmed when the surface of the titanium carbide layer is observed with an optical microscope is 563.7 μm or more. 575.4μm or less The present invention relates to a titanium material characterized in that
[0007] In addition, claims 1 The present invention relates to a titanium container made using the above-described titanium material, characterized in that the titanium container has the above-described titanium carbide layer on its outer surface.
[0008] Also, The method according to claim 1 A method for producing a titanium material having a titanium carbide layer on a surface thereof, comprising the steps of: A first heat treatment step of vacuum heating the titanium material in a carbon-containing atmosphere to a first temperature at which titanium transitions from an α phase to a β phase, and then cooling the titanium material to a temperature lower than the first temperature; a polishing step of polishing a surface of the titanium material after the first heat treatment step; and a second heat treatment step of vacuum heating the titanium material after the polishing step, in a state in which the titanium material is stored in a lidded container or in a carbon-free atmosphere, to a second temperature at which titanium transitions from the α phase to the β phase, and then cooling the titanium material to a temperature lower than the second temperature.
[0009] In addition, claims 3 The method for producing a titanium material described in the above relates to a method for producing a titanium material, characterized in that the vacuum heating in the first heat treatment step and the second heat treatment step is carried out for 15 minutes to 40 minutes.
[0010] In addition, claims 3 This relates to a method for manufacturing a titanium material as described above, characterized in that the titanium material is a container, and the heat treatment process is carried out by placing the titanium material on a flat surface with the opening facing down so as to close the opening.
[0011] In addition, claims 4 This relates to a method for manufacturing a titanium material as described above, characterized in that the titanium material is a container, and the heat treatment process is carried out by placing the titanium material on a flat surface with the opening facing down so as to close the opening.
[0012] Also, The method according to claim 1 A method for producing a titanium material having a titanium carbide layer on a surface thereof, comprising the steps of: A first heat treatment step of vacuum heating the titanium material in a carbon-containing atmosphere to a first temperature at which titanium transitions from an α phase to a β phase, and then cooling the titanium material to a temperature lower than the first temperature; a polishing step of polishing the surface of the titanium material after the first heat treatment step, The titanium material is a container, and the heat treatment step is performed by placing the container on a flat surface with the opening facing down so as to close the opening.
[0013] In addition, claims 3~7 The method for producing a titanium material described in any one of claims 1 to 5 is characterized in that the first heat treatment step is repeated once or a plurality of times after the first heat treatment step and before the polishing step. Effect of the Invention
[0014] Since the present invention is configured as described above, it provides a titanium material, a titanium container, and a method for manufacturing a titanium material that have never been seen before. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view of the present embodiment; [Diagram 2] 1 is a table for comparing the steps of a comparative example and an experimental example. [Diagram 3] 1 is a comparative photograph of the appearance of a comparative example and an experimental example. [Figure 4] 1 shows the results of X-ray diffraction measurements of a comparative example and an experimental example. [Diagram 5] FIG. 5 is an enlarged view of the dashed line portion in FIG. [Figure 6] 1 is a photograph showing examples of colonies in a comparative example and an experimental example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] A preferred embodiment of the present invention will be briefly described below with reference to the drawings to illustrate the operation of the present invention.
[0017] The titanium material according to the present invention can be used, for example, in titanium containers. In this case, for example, the outer surface of the container can be given an elegant texture with a reduced gloss, resistance to fingerprint smudges, and a gray base color.
[0018] That is, although details will be described later, it was confirmed that when the titanium carbide layer is 5 μm or more in thickness, the arithmetic mean roughness (Ra) is 0.90 μm or more, and the average equivalent circular diameter of the area where the twin crystals are aligned is 563.7 μm or more, the surface structure has reduced gloss (a matte finish is imparted), is less susceptible to fingerprint smudges, and has a gray base color.
[0019] Furthermore, the manufacturing method disclosed in Patent Document 1 had problems such as low reproducibility, unstable quality, and low yield, but the present inventors have discovered a manufacturing method that can produce the above titanium material with good reproducibility. EXAMPLES
[0020] A specific embodiment of the present invention will now be described with reference to the drawings.
[0021] In this embodiment, the container is made of titanium and has a titanium carbide layer on its outer surface.
[0022] Specifically, as shown in Fig. 1, this embodiment is a vacuum insulated double container (tumbler) used to store beverages, and is composed of a bottomed cylindrical outer cylinder 1 and a bottomed cylindrical inner cylinder 2 disposed within the outer cylinder 1. The space between the outer cylinder 1 and the inner cylinder 2 is a vacuum insulated space. In the figure, reference numeral 3 denotes a brazing material (titanium brazing) for sealing, and 4 denotes a sealing plate.
[0023] At least the outer surface of the double container (outer cylinder 1) is provided with a titanium carbide layer.
[0024] The titanium carbide layer has a thickness of 5 μm or more and a surface arithmetic mean roughness (Ra) of 0.90 μm or more. When the surface of the titanium carbide layer is observed with an optical microscope, the average equivalent circular diameter of regions (colonies) in which the twins in crystal grains containing twins are aligned is 563.7 μm or more.
[0025] The double container according to this embodiment can be manufactured by carrying out a predetermined process on an outer tube 1 and an inner tube 2 made of commercially pure titanium material (e.g., titanium having a chemical composition belonging to JIS Class 1). Specifically, the outer tube 1 and the inner tube 2 are integrated by welding their opening side ends, and the double container can be manufactured by sequentially carrying out the following steps A to E.
[0026] Step A: The double container is placed in a vacuum furnace with heating function and a vacuum sealing process is performed.
[0027] Specifically, a double container with its mouth welded together is placed on a flat surface with its opening facing down (so as to close the opening), and with brazing material 3 placed around a degassing port 5 at the bottom of the outer tube 1 and a sealing plate 4 placed on the brazing material 3, it is stored in a lidded container (made of stainless steel) and placed in a vacuum furnace. As with the known method disclosed in Patent Document 1 and the like, the inside of the vacuum furnace is heated and depressurized to degas the space between the outer tube 1 and the inner tube 2 and melt the brazing material 3, thereby sealing the space with the brazing material 3 and the sealing plate 4 while keeping it in a vacuum state, forming a vacuum insulation space. Thereafter, a cooling process is performed.
[0028] The degree of vacuum in the vacuum furnace during processing was 10 -3 Torr~10 -4 The pressure is about Torr, the heating temperature is higher than the temperature at which titanium transitions from the α phase to the β phase (about 880°C) (about 1050°C in this embodiment), and the heating time is about 15 to 40 minutes. Cooling is performed by stopping the heating and allowing natural cooling to lower the temperature to below 700°C, then introducing nitrogen gas into the furnace to return the pressure to normal and cool to normal temperature.
[0029] The container is heated above the temperature at which titanium transitions from the α phase to the β phase, and then cooled below that temperature, resulting in the formation of unevenness on the surface of the container like that of pottery, giving it a unique appearance. The entire double container is nitrided using nitrogen gas. The reason for storing the container in a covered container during the vacuum sealing process is to prevent deterioration of the brazing material caused by nitrogen gas. Therefore, if a gas that does not deteriorate the brazing material is used, the process may be carried out without storing the container in a covered container.
[0030] Step B: A vacuum heat treatment is carried out to form a titanium carbide layer.
[0031] This vacuum heat treatment is carried out without placing the double container in a container with a lid, but rather exposing it to the furnace atmosphere in which carbon is present (as in process A, it is carried out by placing it on a flat surface with the opening facing down and blocking the opening).
[0032] For example, by using an appropriate means such as disposing carbon powder in the vacuum furnace or introducing a small amount of carbon gas, the atmosphere in the furnace during heating is made to be a carbon-containing atmosphere, and the inside of the vacuum furnace is heated and reduced in pressure, and then cooled. The degree of vacuum, heating temperature, and heating time are the same as in step A, and cooling is also performed in the same manner as in step A.
[0033] This vacuum heat treatment causes titanium to undergo a transformation from α phase (hcp structure) to β phase (bcc structure) to α phase (hcp structure). During this process, when the dense hcp structure changes to the sparse bcc structure, carbon atoms in the atmosphere penetrate into the voids in the bcc structure, and when the structure returns to the hcp structure, the penetrated carbon atoms are pushed out. The pushed-out carbon atoms accumulate on the surface (the outer surface of the outer tube 1 exposed to the carbon-containing atmosphere), forming a titanium carbide layer.
[0034] Step C: The same vacuum heat treatment as in step B is carried out once or a plurality of times as required (in this embodiment, once).
[0035] Step D: The outer surface of the double container is polished.
[0036] Specifically, the outer surface is polished using an abrasive material and a lathe.
[0037] By carrying out the polishing process, titanium containers with a unique texture formed on the surface with unevenness can be produced with good reproducibility (good yield) (the manufacturing method in Patent Document 1 does not have a polishing process, which is different from the present embodiment).
[0038] Step E: The double container is placed in a container with a lid and subjected to a vacuum heat treatment (as in step A, the container is placed on a flat surface with the opening facing down so that the opening is closed). The container is placed in a container with a lid in order to perform the vacuum heat treatment in an atmosphere with as little carbon as possible, and if the inside of the furnace can be made into a carbon-free atmosphere, the treatment may be performed without placing the double container in the container with a lid.
[0039] The vacuum heat treatment further promotes the growth of twins inside (twins also grow in steps B and C), and when the grown twins reach the surface, the surface is further roughened, making it possible to achieve a configuration with an arithmetic mean roughness (Ra) of 0.90 μm or more and an average equivalent circular diameter of the colonies of 563.7 μm or more. The degree of vacuum, heating temperature, heating time, and cooling are the same as in step A, etc. In this embodiment, the heating temperatures in steps B and C and step E are the same, but they may be different. Similarly, the heating times in steps B and C and step E may be different.
[0040] The titanium vacuum insulated double layer container having the above-mentioned configuration can be manufactured by the above steps A to E. Although the titanium container is described in this embodiment, the present invention can be applied to other titanium products such as a case where a titanium carbide layer is provided on the main surface (widest surface) of a plate material, not limited to the container.
[0041] Furthermore, it is possible to produce titanium containers with a unique texture with good reproducibility by performing at least steps A, B, and D. However, it was confirmed that by performing the step for forming the titanium carbide layer multiple times (performing step C) in addition to steps A, B, and D, and also performing step E for promoting the growth of twin crystals, it is possible to realize a container with a smooth texture, matte feel, and a gray-based appearance.
[0042] Specifically, as shown in FIG. 2, a comparative example produced by sequentially carrying out the above steps A, B, and D (without steps C and E) was compared with an experimental example produced by sequentially carrying out the above steps A to E.
[0043] Figure 3 shows the appearance of the comparative example and the experimental example. It can be seen that the experimental example has less gloss than the comparative example and is mainly gray rather than black. It has also been confirmed that fingerprints are less likely to adhere to the experimental example (less noticeable) than the comparative example.
[0044] Figures 4 and 5 show the results of X-ray diffraction measurements of the comparative example and the experimental example. From these, it can be confirmed that a titanium carbide layer is formed on the surface (the outer surface of the outer cylinder 1) and that twins are generated on the [10-12] plane, as the peak corresponding to the [10-12] plane is shifted to the left (see Figure 5). The thickness of the titanium carbide layer in the comparative example is about 5 μm, and the thickness of the titanium carbide layer in the experimental example is about 10 μm. The hue changes depending on the thickness of the titanium carbide layer on the surface, and the surface roughness changes depending on the degree of twin growth. In the experimental example, the titanium carbide layer becomes thicker by process C, and the twins grow more by process E, which is thought to have resulted in more preferable hue, matte feel, and texture.
[0045] Table 1 shows the results of measuring the size of colonies in the comparative example and the experimental example, and Table 2 shows the results of measuring the surface roughness (arithmetic mean roughness (Ra)). A sample of 3 mm x 7 mm was used, and the areas of colonies that could be confirmed with an optical microscope were calculated using image processing software and converted into equivalent circle diameters (diameters when a certain area is replaced with a perfect circle with the same area), and average values were calculated. An example of a colony observed with an optical microscope is shown in FIG. 6 (the magnifications of the comparative example and the experimental example are the same in FIG. 6). The surface roughness was measured in accordance with JIS B0633 (2001) using a surface roughness measuring instrument (SURFCOM 1500DX 3DF) manufactured by ACCRETECH (Tokyo Seimitsu). The measurement conditions were as follows: measurement length: 4.0 mm, reference length (cutoff value): 0.8 mm, measurement magnification: 2000 times, probe radius: 2 μm, measurement speed: 0.3 mm / s, cutoff type: Gaussian, and tilt correction: least squares linear correction. In addition, "Rolled material" in the table indicates the equivalent circular diameter and surface roughness of the rolled material (plate material) of commercially pure titanium before it is processed into a cylindrical shape.
[0046] [Table 1]
[0047] [Table 2]
[0048] From the above comparison, it can be confirmed that the equivalent circular diameter and Ra of both the comparative example and the experimental example are larger than those of the rolled material, and that the equivalent circular diameter (average diameter) and Ra of the experimental example are both larger than those of the comparative example. The average colony diameter (563.7 μm) and Ra (0.90 μm) of the comparative example still provide a favorable appearance, but when the values of the comparative example are exceeded (for example, the average colony diameter of 575.4 μm and Ra of 1.70 μm in the experimental example), it is believed that an even better appearance will be presented, and that steps C and E will be necessary to obtain the values of the experimental example.
[0049] Since this embodiment is constructed as described above, it is an unprecedented titanium container that has a subdued luster, is less susceptible to fingerprint smudges, and has a refined texture with a gray base.
Claims
1. A titanium material having a titanium carbide layer on a surface thereof, The titanium carbide layer has a thickness of 5 μm or more and an arithmetic mean surface roughness (Ra) of 0.90 μm or more; A titanium material characterized in that the average equivalent circular diameter of the area in which the twins are aligned in a crystal grain containing the twins, as confirmed when the surface of the titanium carbide layer is observed with an optical microscope, is 563.7 μm or more.
2. 2. The titanium material according to claim 1, wherein the titanium carbide layer has a thickness of 10 [mu]m or more.
3. 2. The titanium material according to claim 1, wherein the titanium carbide layer has a surface arithmetic mean roughness (Ra) of 1.70 μm or more.
4. 3. The titanium material according to claim 2, wherein the titanium carbide layer has a surface arithmetic mean roughness (Ra) of 1.70 μm or more.
5. 5. The titanium material according to claim 1, wherein the titanium carbide layer has an average equivalent circle diameter of 575.4 μm or more in the region where the twin crystals are aligned.
6. A titanium container made using the titanium material according to any one of claims 1 to 4, characterized in that the titanium container has the titanium carbide layer on its outer surface.
7. 6. A titanium container made of the titanium material according to claim 5, characterized in that said titanium carbide layer is provided on an outer surface of said titanium container.
8. A method for producing a titanium material having a titanium carbide layer on a surface thereof, comprising the steps of: A first heat treatment step of vacuum heating the titanium material in a carbon-containing atmosphere to a first temperature at which titanium transitions from an α phase to a β phase, and then cooling the titanium material to a temperature lower than the first temperature; a polishing step of polishing a surface of the titanium material after the first heat treatment step; A method for producing a titanium material, comprising:
9. 9. The method for producing a titanium material according to claim 8, further comprising a second heat treatment step of vacuum heating the titanium material, after the polishing step, in a state in which the titanium material is stored in a covered container or in a carbon-free atmosphere, to a second temperature at which titanium transitions from the alpha phase to the beta phase, and then cooling the titanium material to a temperature lower than the second temperature.
10. 10. The method for producing a titanium material according to claim 9, wherein the vacuum heating in the first heat treatment step and the second heat treatment step is carried out for 15 minutes to 40 minutes.
11. 11. The method for producing a titanium material according to claim 8, wherein the first heat treatment step is repeated once or a plurality of times after the first heat treatment step and before the polishing step.
12. 11. A method for producing a titanium material according to claim 8, wherein the titanium material is a container, and the heat treatment step is carried out by placing the titanium material on a flat surface with an opening facing down so as to close the opening.
13. 12. A method for producing a titanium material according to claim 11, wherein the titanium material is a container, and the heat treatment step is carried out by placing the titanium material on a flat surface with an opening facing down so as to close the opening.
Citation Information
Patent Citations
Surface carburization technique of medical titanium alloy femoral head in total hip arthroplasty
EP1980640A2
JP1975051039A
Surface hardened metal and its manufacture
JP1983161771A
Surface treatment of titanium
JP1987139861A
METHOD FOR STRENGTHENING beta TYPE TITANIUM ALLOY AND betaTYPE TITANIUM ALLOY PRODUCT OBTAINED THEREBY
JP2006097115A